Pengiriman Pesan Whatsapp Massal Otomatis dengan XPath Address Finder, Checker, dan Fitur Update - Hartanto Putra, Yohannes Dimas; Ghofir, Abdul (Jurnal Informatika: Jurnal Pengembangan IT, 2022)
WhatsApp is a reliable, secure, simple calling and messaging service that is available for free. This service was originally developed as the short message service alternative, and now supports location, document, video, photo, and text exchange features. This service has over two billion active users in one hundred and eighty countries. With some of these advantages, this service can be used as an alternative to SMS to convey information in bulk. For example, broadcasting information or reminders of certain things or advertising. By using WhatsApp, the costs required for the broadcasting process will be very small compared to using SMS. However, it would be very inefficient and time-consuming if the process of broadcasting the information was still done manually by retyping or copy-pasting messages from target to target. This reseach aims to develop an application that can automate the process of sending mass messages automatically through the WhatsApp service. In addition, a Virtual Contact File creation feature was also developed to help users add contacts from targets. To improve the adaptability to HTML structure changes on the WhatsApp Web website, an XPath address update feature on key elements was also developed. To support the update feature, the XPath address finder and checker on certain elements in a web page function were also developed.